IMPLEMENTASI REWARD STAMP DALAM MENUMBUHKAN SEMANGAT SANTRI PADA HAFALAN JUZ ‘AMMA DI TPQ AL – WALAD CIPONDOH KOTA TANGERANG - Putri Aulia Rahman; Busahdiar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The research problem in this study lies in the low level of enthusiasm among early-age students in memorizing Juz ‘Amma. This condition is indicated by the inconsistency of memorization, the tendency to lose focus during the recitation submission process, and the lack of enthusiasm in adding new memorization. These conditions require a learning strategy that can foster students’ learning enthusiasm. Therefore, this study aims to analyze the types of reward stamps, their impacts, as well as the challenges and obstacles in their implementation in fostering students’ enthusiasm in memorizing Juz ‘Amma at Taman Pendidikan Al-Qur’an (TPQ) AL - WALAD Cipondoh, Tangerang City. This research employs a qualitative approach using a descriptive method. Data were collected through observation, interviews, and document studies. The data analysis in this study used an interactive model which includes the stages of data reduction, data presentation, and conclusion drawing. The validity of the data was tested through credibility methods, particularly by applying a triangulation approach. The results of the study show that the type of reward stamp implemented at Taman Pendidikan Al-Qur’an (TPQ) AL - WALAD Cipondoh is in the form of tiered star stamps used as an appreciation for students’ efforts and processes in memorizing Juz ‘Amma. The provision of reward stamps has a positive impact on fostering students’ enthusiasm, as reflected in increased enthusiasm, self-confidence, activeness, and courage in submitting their memorization. However, its implementation also faces several challenges, such as differences in students’ abilities, limited time, students’ emotional conditions, and student absenteeism. These challenges are addressed by teachers through individual approaches, positive reinforcement, and the gradual and fair management of reward stamps.